Regular arrays of highly ordered ferroelectric polymer nanostructures for non-volatile low-voltage memories - Hu, Zhijun; Tian, Mingwen; Nysten, Bernard; Jonas, Alain M. (Nature materials, 2009)
Ferroelectric nanostructures are attracting tremendous interest because they offer a promising route to novel integrated electronic devices such as non-volatile memories and probe-based mass data storage. Here, we demonstrate that high-density arrays of nanostructures of a ferroelectric polymer can be easily fabricated by a simple nano-embossing protocol, with integration densities larger than 33 Gbits inch −2 . The orientation of the polarization axis, about which the dipole moment rotates, is simultaneously aligned in plane over the whole patterned region. Internal structural defects are significantly eliminated in the nanostructures. The improved crystal orientation and quality enable well-defined uniform switching behaviour from cell to cell. Each nanocell shows a narrow and almost ideal square-shaped hysteresis curve, with low energy losses and a coercive field of ∼10 MV m −1 , well below previously reported bulk values. These results pave the way to the fabrication of soft plastic memories compatible with all-organic electronics and low-power information technology. Ferroelectric polymers are of interest for use as memory devices for all-organic electronics applications. A fast and efficient embossing technology is now shown not only to lead to high-density arrays of ferroelectric nanocells but also to significantly improve the ferroelectric properties of these structures.